The Sacred Fig as Cosmic Nexus in Hindu Tradition - Bhusal, Damodar (SNPRC Journal, 2024)
The Ficus religiosa, or Sacred Fig, holds a profound place in Hindu tradition, revered as a cosmic nexus that bridges divine, human, and natural realms. This article explores its significance within Hindu Puranic texts, highlighting its role in embodying a sophisticated human-plant symbiosis and an implicit recognition of plant sentience. The problem addressed is the anthropocentric bias that often overlooks vegetal agency in cultural narratives. By employing Michael Marder’s Plant Humanities and Matthew Hall’s “plants as persons” framework, the study argues that the Peepal tree transcends its biological identity, functioning as a divine abode, cosmic axis, and ritual partner. The methodology involves analyzing key Puranic narratives, such as those in the Skanda, Padma, and Bhagavata Puranas, which depict the tree as a living temple of the Trimurti, a mediator between worlds, and a subject of rituals like circumambulation and offerings. Findings reveal that these texts articulate the Peepal’s sacred status through its association with deities, cosmic order, and ethical prohibitions against harm, reflecting a deep respect for its intrinsic value. This resonates with contemporary plant philosophy, challenging dualistic views and affirming plants’ dynamic agency. The implications suggest that Hindu traditions offer a blueprint for re-evaluating human-plant relationships, fostering ecological ethics and holistic perspectives relevant to modern environmental thought.